Digital preservation of business assets as a risk management strategy - Coutinho, C. (Proceedings of the Workshop on Open Source and Design of Communication (ACM/OSDOC 2013), 2013)
The effect of a new globalised world where technologies and methodologies mature rapidly is a constant change in business paradigms and assets. Tools, technology and formats become easily deprecated and replaced by others, and legal and licensing affairs are subject to constant legislation changes. Hence, a business seeking to preserve its assets for long term becomes very prone to problems of this nature. This paper presents an approach to analyse the risks coming from various sources which may affect enterprise business continuity, discussing the problems and issues relevant to it, and proposing long-term digital preservation as a mitigation action to handle some of these determined risks, and the implementation of a framework to support these concepts, in the context of the Seventh Framework Programme (FP7) TIMBUS project.